AB0230 Pre-methotrexate lung screening for interstitial lung disease – is a chest x-ray adequate?. (23rd January 2014) - Al-Shakarchi, I.; Lobão, B.; Henriques, C.; Steer, S.; Gordon, P.; Irving, K.
Abstract : Background: Methotrexate (MTX) is the most commonly used disease modifying anti-rheumatic drug (DMARD) for the treatment of rheumatoid arthritis (RA). Methotrexate pneumonitis (MP) is a potentially fatal hypersensitivity reaction with a mortality rate of ∼20%, the risk being maximal in the first year of treatment. The incidence of MP is higher in patients with pre-existing lung disease, particularly interstitial lung disease (ILD). Early identification of these patients provides the opportunity to offer an alternative agent. Prior to commencing MTX the current British Society for Rheumatology guidelines advise a screening chest radiograph (CXR). CXR has a low sensitivity for detecting ILD and it has been suggested that carbon monoxide transfer factor (TLCO) is a more sensitive marker. The guideline of the Rheumatology department at King's College Hospital is to request a pulmonary function test (PFT) as well as a CXR prior to commencing MTX in all RA patients. If the TLCO is abnormal a high-resolution computerised tomography scan (HRCT) is considered. Objectives: To investigate whether screening with PFT and CXR identifies more patients with ILD than screening with CXR alone. Methods: 107 MTX-naive RA patients aged 21–86 who had previously had CXR and PFT were identified from the hospital database. Those patients with an abnormal TLCO (defined as ≤79% in non-smokers and ≤69% in smokers) who had undergone HRCT were included. Where ILD was identified on HRCT, the CXR was reviewed for abnormalities. Results: Of the 107 patients, 44 with normal TLCO were excluded and a further 23 patients were excluded as they had not had HRCT. Of the 40 remaining patients, ILD was identified in 12 (see Table ) of whom 6 (50%) had a normal CXR. 9 (75%) patients had early RA, defined as within 3 years of symptom onset. Of the 6 patients with abnormal CXR, 5 had TLCO <49% indicating advanced lung disease. Conclusions: Our results show that the combination of CXR and PFT detects more patients with RA ILD compared to CXR alone, particularly in less advanced respiratory disease. In this cohort of RA patients undergoing pre-MTX screening we identified 12 patients with ILD, a prevalence of 11%. 50% of these patients would not have been identified by screening with CXR alone. MP is a rare but potentially fatal side-effect of MTX treatment. It is well recognized that prognosis is significantly worse in RA patients with ILD. Therefore we suggest early screening with PFT to identify these patients, allowing appropriately tailored management. References: Disclosure of Interest : None Declared